Implementation of The Duties and Functions of The Village Consultative Body (BPD) in Cilimus Village, Kuningan Regency - Reza Rahmat Nur Aziz; Ayub Maulana Sidiq; Moh Taufik Hidayat; RM Haryo Bharoto (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the implementation of the duties and functions of the Village Consultative Body (BPD) in Cilimus Village, Kuningan Regency, particularly in accommodating and conveying community aspirations and planning development programs. The formation of BPD as a community representative within village governance is intended to accommodate and convey community aspirations. For program planning to be directly felt by the community, BPD should involve the community in planning programs to be implemented. Additionally, BPD has duties and functions in discussing and agreeing on Village Regulation (PerDes) drafts. As observed in the BPD of Cilimus Village, Kuningan Regency, the duties and functions of BPD have not run optimally, particularly in accommodating aspirations and the lack of initiative from BPD members in drafting and discussing PerDes. This research attempts to identify the duties and functions of BPD in carrying out their tasks and identify obstacles faced by the Village Consultative Body (BPD) in Cilimus Village, Kuningan Regency. This study aims to examine how the duties and functions of the Village Consultative Body (BPD) in Cilimus Village are implemented using qualitative methods. It is expected that after this research, BPD in Cilimus Village, Kuningan Regency, will be able to carry out their duties and functions as expected.